Ablation of atrial fibrillation: single-shot techniques poised to dominate rhythm control strategies/the future is here - Manolis, Antonis S. (J Thorac Dis, 2017)
Over the recent years, the advent of single-shot techniques, such as circular catheter and cryoballoon ablation, has ushered in a new era in the catheter ablation approach and rhythm control strategies of patients with atrial fibrillation (AF). These techniques make it easier to navigate the heart and have the potential to decrease the threshold for, expand the access to, and increase patient and physician acceptance of rhythm-control therapies, that may lead to reduction of the AF disease burden and its socioeconomic impact. Due to technical issues the circular catheter technique is lagging behind, however the cryoballoon approach is progressing at a faster pace both in the field of technical advancements and clinical studies, all contributing to its rapid penetration in the electrophysiological community and rhythm management approaches toward the commonest cardiac arrhythmia. Comparative studies of the conventional point-by-point radiofrequency (RF) ablation technique and the cryoablation approach to pulmonary vein isolation (PVI), which constitutes the cornerstone of all ablation methods, seem to favor the cryoablation technique in certain aspects. The results of current studies converge in their conclusion that cryoablation employing current generation cryoballoons is a simplified and faster method compared to the conventional technique in achieving effective and durable PVI. Furthermore, investigators have recently proposed particular tips and parameters to serve as reliable predictors of successful and durable PVI that may enhance the clinical success of this single-shot ablation technique. These issues will be discussed in this overview and placed into perspective.